Present Tense Narration in Contemporary Fiction : A Narratological Overview - Huber, Irmtraud (Palgrave Macmillan, 2016)
In this book, Irmtraud Huber considers a wide range of contemporary novels to explore the variety of possibilities and effects of the use of the present tense, as well as investigating the reasons for its popularity. By illustrating the complexity and sophistication of four different types of contemporary usage, Huber’s discussion goes some way towards refuting those critical voices which consider present-tense narration a passing fad and stylistic affectation. As a tense of narration, the present can serve to tell different stories than the past tense, or can tell them differently. By no means a passing fad, it is an important characteristic of contemporary literature.
Keywords: contemporary fiction; twenty-first century literature; narrative fiction; first person narrative; present tense narrative; narrative deictic; retrospective and simultaneous narration; interior monologue; historical present tense; 800